PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KINERJA MANAJERIAL DENGAN SISTEM PENGUKURAN KINERJA SEBAGAI PEMEDIASI PADA PT. PLN (Persero) UP3 SEMARANG - Ciptaningtias, Arum Febriyanti; Widyarti, Maria Theresia Heni; Ramantika, Eurico (EconBank: Journal of Economics and Banking, 2023)
This study aims to determine the effect of the dimensions of Total Quality Management on managerial performance mediated by a performance measurement system. The sampling technique in this study used a purposive sampling technique. Methods of data collection using questionnaires and interviews. Path analysis technique was used to examine the effect of Total Quality Management dimensions (customer focus, obsession on quality, education and training, teamwork, continuous improvement) on managerial performance mediated by the performance measurement system at PT. PLN (Persero) UP3 Semarang. The results of the direct influence test show that Total Quality Management on the dimensions of customer focus, and obsession on quality has an effect on managerial performance. Meanwhile, education and training, teamwork, and continuous improvement have no effect on managerial performance. Then Teamwork and continuous improvement affect the performance measurement system. But Focus on Customers, Obsession on quality, Education and training have no effect on the performance measurement system. The results of the indirect effect test show that the performance measurement system is not able to mediate Total Quality Management on managerial performance.